2015
DOI: 10.1073/pnas.1504144112
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation between Satb2 and Fezf2 promotes subcerebral projection neuron identity in the developing cerebral cortex

Abstract: Generation of distinct cortical projection neuron subtypes during development relies in part on repression of alternative neuron identities. It was reported that the special AT-rich sequencebinding protein 2 (Satb2) is required for proper development of callosal neuron identity and represses expression of genes that are essential for subcerebral axon development. Surprisingly, Satb2 has recently been shown to be necessary for subcerebral axon development. Here, we unravel a previously unidentified mechanism un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 48 publications
6
75
0
Order By: Relevance
“…We also observed instances of the same gene being activated and repressed by TBR1, i.e., Ank2 and Scn2a1, at different time points. In addition to observing this in a previous study (McKenna et al 2015), the fact that we observe the same trend of activation and repression across RISH in situ, DIG in situ, and RT-qPCR gives us confidence that such temporal changes in regulation are possible, perhaps due to different roles of TBR1 in different cell types, but understanding this phenomenon will require further study. Finally, the changes in expression were observed in homozygous mutant mice, whereas the LoF mutations observed in ASD probands affect a single allele.…”
Section: Tbr1 Regulates Autism Risk Genessupporting
confidence: 77%
See 1 more Smart Citation
“…We also observed instances of the same gene being activated and repressed by TBR1, i.e., Ank2 and Scn2a1, at different time points. In addition to observing this in a previous study (McKenna et al 2015), the fact that we observe the same trend of activation and repression across RISH in situ, DIG in situ, and RT-qPCR gives us confidence that such temporal changes in regulation are possible, perhaps due to different roles of TBR1 in different cell types, but understanding this phenomenon will require further study. Finally, the changes in expression were observed in homozygous mutant mice, whereas the LoF mutations observed in ASD probands affect a single allele.…”
Section: Tbr1 Regulates Autism Risk Genessupporting
confidence: 77%
“…In addition, when we merged the high-confidence gene sets, we found that TBR1 bound 82 regions adjacent to 25 of the 34 high-confidence ASD genes (74%, binomial P-value: 1.11 × 10 −4 , hypergeometric P-value: 2.81 × 10 −8 ). We previously performed ChIP-seq in E14.5 neocortex for EP300 (Wenger et al 2013), a transcriptional co-activator that marks active enhancers, and ChIP-seq in E15.5 neocortex for SATB2 (McKenna et al 2015), another master regulator of cortical development. The TBR1 high-confidence ASD gene enrichment is stronger, by either the binomial or hypergeometric test, than the enrichments for EP300 or SATB2.…”
Section: Tbr1 Binds Near High-confidence Asd Genes In the Developing mentioning
confidence: 99%
“…1 + neurons in the lower CP (5.96-fold; n = 3; P < 0.001), upper CP (2.56-fold; P < 0.001), and overall (3.62-fold; P < 0.001) (Fig. 1 J, + neurogenesis (8). Indeed, although Satb2 was preferentially expressed in the upper CP (layers II-IV) in all genotypes ( Fig.…”
Section: ;Ascl1mentioning
confidence: 86%
“…Tbr1, a T-box transcription factor expressed in layer VI, specifies a corticothalamic neuronal fate (3) and also represses the expression of Fezf2, a zinc finger transcription factor that specifies a layer V subcerebral identity (4,5). Fezf2 represses Tbr1 expression and a corticothalamic fate in layer V neurons (6,7) and also represses the expression of Satb2 (8), an AT-rich DNA-binding protein that specifies a layer II-IV callosal identity (9,10). In layer II-IV callosal neurons, Satb2 represses the expression of Ctip2/Bcl11b, a zinc finger transcription factor that controls layer V subcerebral projection patterns (11,12).…”
Section: Deep-layer Neurogenesis While Reducing Satb2mentioning
confidence: 99%
“…For example, Shim et al (2012) identified a region 7.3 kb downstream of the Fezf2 TSS termed the E4 enhancer, which is the region at which activators of Fezf2 , SOX4 and SOX11, compete for binding with repressor SOX5. SATB2 also binds this enhancer and positively regulates the expression of Fezf2 in cortical neurons (McKenna et al, 2015). This enhancer is most strongly expressed in cortical progenitors and possibly drives the expression of FEZF2 in these cells (Eckler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%